Investigation and Analysis of People Preferences in Choosing Public Transportation During COVID-19 Pandemic: Statistical Approach and Case Study in Malang City - Amrullah, Ivan Fadhil; Mudjanarko, Sri Wiwoho (Universitas Ibn Khaldun Bogor, 2023)
The transportation condition in Malang City during COVID-19 pandemic has been the subject of this research, with one study proposing to support information about public transportation services in the city. This policy encourages people to participate in activities such as working from home and school during the COVID-19 pandemic. Another concern is that the availability of public transportation facilities is being limited by a lack of conventional transportation as result of this policy. The greatest impact on this variable is the appropriateness of the price, as customers of the service are typically users on a daily basis. Online transportation is considered more effective in terms of distance because there is a mapping application or location that is provided by service providers or drivers in specific areas. The coefficient of determination is a statistical measure used to evaluate the accuracy of a model in predicting future outcomes. The model is generally accurate because all of the variables are significant and have a direct effect on the dependent variables. The F-test value associated with the coefficient was 33.927, and the level of significance was >0.0001. The following describes the results of the t-test regarding the effect of variables on variables: Reliability The value of the t-count is 2.358 > 1.68, and the significance value is 0.013 < 0.05. Responsiveness The t-count of 9.513 is greater than 1.68, and the associated significance level is 0.0001 which is less than 0.05.